A Simple, Efficient Synthesis of 2-Aryl Benzimidazoles Using Silica Supported Periodic Acid Catalyst and Evaluation of Anticancer Activity. (24th April 2013) - Sontakke, Vyankat A.; Ghosh, Sougata; Lawande, Pravin P.; Chopade, Balu A.; Shinde, Vaishali S.
Abstract : A new, efficient method for the synthesis of 2-aryl substituted benzimidazole by using silica supported periodic acid (H5 IO6 -SiO2 ) as a catalyst has been developed. The salient feature of the present method includes mild reaction condition, short reaction time, high yield and easy workup procedure. The synthesized benzimidazoles exhibited potent anticancer activity against MCF7 and HL60 cell lines.